Pengaruh Pembelajaran Kontekstual Integratif Agama dan Budaya terhadap Motivasi Belajar Ilmu Pengetahuan Alam dan Sosial di Sekolah Dasar Negeri Kawisrejo - Nahdiah Nur Fauziah; Alvi Syafa'atu Rosidah; Anzilna Qotrun Nada; Akhiyat Akhiyat; Fathiyaturrahmah Fathiyaturrahmah (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study investigates the effectiveness of contextual learning integrated with religious and cultural values in enhancing students’ motivation in studying Ilmu Pengetahuan Alam dan Sosial (IPAS) at the elementary level. The research was driven by the recurrent issue of low student motivation in IPAS, which is often perceived as monotonous due to its emphasis on memorization rather than meaningful comprehension. Employing a quantitative approach with a quasi-experimental nonequivalent control group design, the study involved 28 fifth-grade students, divided equally into experimental and control classes. Data were collected through a validated motivation questionnaire using a five-point Likert scale and analyzed using normality testing, homogeneity testing, and an independent samples t-test via SPSS 25. The findings indicate a significant effect of integrating religious and cultural contexts into IPAS instruction, as demonstrated by a t-test significance value of 0.000 < 0.05 and an average score difference of 11.571 points between groups. These results suggest that contextualizing IPAS material with religious and cultural dimensions fosters higher engagement and learning enthusiasm. Consequently, contextual learning that incorporates religion and culture emerges as an effective pedagogical strategy for improving motivation in IPAS learning within Islamic elementary schools.